HUBUNGAN IKLAN, PENJUALAN PRIBADI, DAN PROMOSI TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN KECAP ABC (STUDI KASUS DI WILAYAH RT.13 RW.02 RAWA BUAYA CENGKARENG) - Iswandir Iswandir (JURNAL MITRA MANAJEMEN, 2020)
ABSTRACTThis study aims to understand and analyze the influence of advertising, personal selling, and sales promotion toward purchasing decision of ABC sweet soy sauce (case study in RT.13 RW.02 Rawa Buaya Cengkareng Area). The analytical tool used is multiple linear regression with SPSS version 21 statistical software. The sampling technique uses the non probability sampling method by purposive sampling. The population in this study were residents of RT.13 RW.02 Rawa Buaya, Cengkareng. The results showed that advertising variables partially has no significant effect on purchasing decisions of ABC sweet soy sauce known from the sig. 0.319 > 0.05. Personal selling variables partially have no significant effect on purchasing decisions of ABC sweet soy sauce known from the sig. 0.052 > 0.05. Sales promotion variables partially have a significant effect on purchasing decisions of ABC sweet soy sauce known from the sig. 0.000 < 0.05. While, the advertising, personal selling, and sales promotion variables simultaneously had a significant effect on ABC sweet soy sauce purchasing decisions. This is based on the sig. 0.000 < 0.05. From the regression results, it is known that R is 0.771 which means that there is a strong relationship between the variables of advertising, personal selling, and sales promotion of ABC sweet soy sauce purchasing decisions. Meanwhile, the Adjusted R Square value of 0.582 means 58.2% indicates that the independent variable contributes to the influence of the dependent variable. While the remaining 41.8% is influenced by other factors not included in this research model. Keyword: advertising, personal selling, sales promotion, purchasing decision.